Feasibility of a syndrome‐informed micro‐intervention for infants with Down syndrome. Issue 4 (31st January 2021) - Fidler, D. J.; Schworer, E. K.; Needham, A.; Prince, M. A.; Patel, L.; Will, E. A.; Daunhauer, L. A.
Abstract: Background: Infants with Down syndrome (DS) are at risk for a range of phenotypic outcomes, including delays in the onset of reaching behaviour, a critical skill that facilitates early learning. This parallel‐group feasibility and pilot study presents findings from a parent‐mediated micro‐intervention that aimed to support the development of reaching behaviour in a sample of infants with DS. Methods: Participants were 73 infants with DS and their caregivers. Infants who qualified for the home‐based intervention (based on manual skill performance on Bayley Scales of Infant and Toddler Development, Third Edition items) were randomly assigned individually or by geographical region to a treatment or an alternative treatment condition that involved toy‐based interactions with caregivers. Infants in the treatment condition experienced facilitated reaching during the toy‐based interactions through the use of Velcro‐affixed mittens and toys. Results: Forty‐two infants met criteria to participate in the intervention, and 37 participated in both baseline and post‐treatment visits. At post‐treatment, infants in the treatment condition demonstrated shorter latencies to make contact with objects and showed higher frequencies of reach attempts and swats at objects than infants in the alternative treatment group. These findings were more pronounced when examining a chronological age‐restricted subgroup of infants 5 to 10 months. Conclusions: Findings suggest that a syndrome‐informed approach to targeted intervention may be a promising application of phenotyping science in DS and other neurogenetic conditions associated with intellectual disability.